Taxonomic and Ecological Description of Some Coccinellides - Mirzaliev Abdujabbor Mamatyusuf o‘g‘li; Nazirov Bahodir Baxtiyorovich; Bo'riyev Abdumo'min Rasulovich (Genius Publishing Group, 2022)
The article focuses on the biological fight against pests of fruit trees, which, on the same day, become a problem with dolizarb. This article specifically explored the features of Coccinellid beetles in the specified area, such as seasonal development, the life cycle, the degree of exposure to pests.
Keywords: Zararkunanda; Coccinellid; entomofag; Harmonia oxyridis Pallas